The Effect of Ice Breaking and Rewards on Chemistry Students' Learning Outcomes in Basic Chemistry Courses - Zuhrah Adminira Ruslan (Asian Journal of Applied Education (AJAE), 2026)
Chemistry learning in higher education often encounters low student participation and boredom, affecting learning outcomes. This study examines the effect of ice breaking and rewards on student achievement in Basic Chemistry courses. A quantitative quasi-experimental design was applied, with purposive sampling to form experimental and control groups. The intervention, consisting of ice breaking and rewards as motivational reinforcement, was conducted over eight meetings. Data were collected using valid and reliable written tests and analyzed inferentially. Results indicate that the experimental group achieved a higher mean score (79.74) than the control group (73.03), with a significant difference t(33)= 4.854; p < 0.001 and a large effect size (1.41), confirming the effectiveness of the strategy.